SAT0268 Effect of long-term TNF blockage on lipid profile in ankylosing spondylitis patients. (23rd January 2014) - Moraes, J.C.; Souza, F.H.C.; Ribeiro, A.C.D.M.; Saad, C.G.S.; Calich, A.L.; Silva, C.A.; Bonfa, E.
Abstract : Background: Ankylosing spondylitis (AS) patients have increased cardiovascular (CV) morbidity and mortality. Lipid profile plays an important role in development of CV disease and there are no data regarding prospective long-term evaluation of lipid profile in AS patients under TNF blockers. 1 Objectives: to evaluate prospectively the long-term effect of TNF blockage therapy on lipid profile in AS patients and its possible association with clinical and disease parameters. Methods: Thirty-seven consecutive AS patients, who were eligible to receive anti-TNF therapy, were prospectively enrolled. All patients were treated with TNF blockers during the follow-up period, and they were evaluated for lipid profile, atherogenic index (AI), body mass index (BMI), waist circumference and disease parameters at baseline and at 52 and 104 weeks after treatment. Patients using statins or with concentration of LDL cholesterol >160 mg/dL were considered at risk. 2 Data are expressed in means ± standard deviation or medians (interquartile ranges) as appropriate. For continuous variables, one-way Anova or Kruskal-Wallis analysis of variance was used with a significance level p<0.05. Results: Evaluation of lipid profile during the follow-up period revealed a significant increase in levels of LDL cholesterol (98±27mg/dL vs. 109±30 mg/dL vs 117±33 mg/dL, p=0.029) and a trend for an increase in total cholesterol in the same period (168±33 mg/dL vs. 181±35 mg/dL vs. 187±39mg/dL, p=0.057). No changes were found in the concentration of HDL cholesterol (45 (37-58) mg/dL vs. 48 (42-61) mg/dL vs. 50 (43-59) mg/dL p=0.20) and triglycerides (93 (75-133) mg/dL vs. 88 (72-118) mg/dL vs. 95 (76-125) mg/dL p=0.84) or in AI (3.7±1.1 vs. 3.7±0.9 vs. 3.8±1.0 p=0.87) was observed. The proportion of patients considered at risk remained unchanged (5.5% vs. 13.5% vs. 16.2%, p=0.24). BMI (26.0±4.6 kg/m 2 vs. 26.4±4.6 kg/m 2 vs. 26.7±4.9 kg/m 2, p=0.78) and waist circumference (89.7±12.6 cm vs. 92.1±12.2 cm vs. 94.1±12.7 cm, p=0.49) values remained stable throughout the study. Treatment with TNF blockers improved all disease parameters: BASDAI (p<0.001), BASFI (p<0.001), ASQoL (p=0.004), C-reactive protein (p<0.001), and erythrocyte sedimentation rate (p<0.001). Conclusions: The novel demonstration that anti-TNF therapy has a long-term deleterious effect in LDL cholesterol levels in AS patients, reinforces the recommendation for a close monitoring and early intervention in this modifiable cardiovascular risk factor. References: Bremander A, Petersson IF, Bergman S, et al. Population-based estimates of common comorbidities and cardiovascular disease in ankylosing spondylitis. Arthritis Care Res (Hoboken) 2011;63:550–6. Lipsy RJ. The National Cholesterol Education Program Adult Treatment Panel III guidelines. J Manag Care Pharm 2003;9:2-5. Disclosure of Interest: None Declared